A Full-bridge Director Switches based Multilevel Converter with DC Fault Blocking Capability and Its Predictive Control Strategy - Jin Zhu; Tongzhen Wei; Qunhai Huo; Jingyuan Yin (Energies, 2018)
Voltage source converter-based high-voltage direct current transmission system (VSC-HVDC) technology has been widely used. However, traditional half-bridge sub module (HBSM)-based module multilevel converter (MMC) cannot block a DC fault current. This paper proposes that a full-bridge director switches based multi-level converter can offer features such as DC side fault blocking capability and is more compact and lower cost than other existing MMC topologies. A suitable predictive control strategy is proposed to minimize the error of the output AC current and the capacitor voltage of the sub-module while the director switches are operated in low-frequency mode. The validity of the proposed topology and control method is demonstrated based on simulation and experimental studies.